A DC Motor Position Control System in a 3D Real-Time Virtual Laboratory Environment Based on NCSLab 3D - Lei, Zhongcheng; Hu, Wenshan; Zhou, Hong; Zhong, Liang; Gao, Xingran (International Journal of Online and Biomedical Engineering (iJOE), 2015)
Virtual laboratories and remote laboratories have been a great complement of traditional laboratories in the last few decades. Virtual laboratories, which use computer technology to perform experiments utilizing virtual instrumentation instead of physical devices, are warmly welcomed for its low-cost advantage, 24/7 operation, remotely accessibility and sharing features. In this paper, a DC motor control system which can be used to carry out the experiments of position control in real time based on NCSLab framework is presented. After describing the process of 3D modelling, rendering in Flash 3D engine and control algorithms that are generated using Matlab Real-Time Workshop, a position control experiment is conducted and the experimental results are demonstrated as an example. For most virtual control laboratories, users are only allowed to design the algorithms and then monitor the control results. However, wiring process which is also an important part of practical control experiments cannot be emulated. To address this problem, a new experiment modelling method which allows the users to do the wiring in the 3D real-time virtual laboratory is proposed in this paper. It could make users feel more sense of reality and immersion when performing the virtual experiments.